Mental health and help-seeking: Experiences of international student-athletes competing in national collegiate athletic association division i - Hayashi, E. F.; Hoffmann, M. D.; Brice, J. E.; Wilson, K. S. (Journal of Clinical Sport Psychology, 2026)
This study qualitatively examined the mental health and help-seeking experiences and perspectives of international student-athletes through the lens of Ryba et al.`s cultural transition model. Fifteen male ( n = 7) and female ( n = 8) National Collegiate Athletic Association Division I international student-athletes from 13 countries participated in one-on-one semistructured interviews. Using reflexive thematic analysis, themes were generated pertaining to athletes: (a) early experiences with mental health stigma, (b) pretransition, (c) acute cultural adaptation, and (d) sociocultural adaptation. The core findings highlighted athletes` experiences moving through three phases of cultural migration to the United States. The first phase highlighted athletes` varied emotions (e.g., sadness, optimism) before migration, which did not involve mental health struggles. The second phase emphasized cultural adaptation challenges, shifts in mental health and support systems, and help-seeking barriers and facilitators. Finally, the third phase involved generally improved athlete mental health and help-seeking attitudes, with evolving coach-athlete relationships influencing program transfer decisions.